Pemodelan Struktur Lapisan Bawah Permukaan Berdasarkan Tahanan Jenis di Dusun Rombo Desa Saukang Kecamatan Sinjai Timur Kabupaten Sinjai Provinsi Sulawesi Selatan - Aqil Naufaldy Rifanzha; Muh Said Lanto; Minarti Minarti (Jurnal Fisika Unand, 2024)
Research has been carried out which aims to model the structure of the subsurface layers in Rombo Hamlet, Saukang Village, East Sinjai District, in Sinjai Regency. This research uses the resistivity geoelectric method of the Wenner-Schlumberger configuration. The number of measurement paths consists of five tracks, each 150 m. The geology of the research location includes the Walanae Formation, which consists of sandstones, conglomerates, tuffs, siltstones, claystones, limestones, and marls. The results of the study allegedly show that the subsurface structure consists of several layers with interpretations in the form of groundwater aquifers, sandstones, and claystones. The first track shows a resistivity value of 0.753 Ωm to 3.22 Ωm where there are free aquifers at a depth of 1.25 meters to 24.0 meters, the second track has free aquifers and confined aquifers with resistivity values of 0.976 Ωm to 3.75 Ωm which are at a depth of 1.25 meters to 28.7 meters, the third track shows a resistivity value of 0.643 Ω to 2.46 Ωm there are free and confined aquifers that spread at depths of 15.9 meters to 28.7 meters, the fourth line has free aquifers and aquifers The depressed aquifer which has a resistivity value of 1.83 Ωm to 6.27 Ωm is at a depth of 5.19 meters to 28.7 meters, while on the fifth line at a depth of 1.25 meters to 28.7 meters there are free aquifers and confined aquifers which have resistivity value of 0.801 Ωm to 4.10 Ωm.